Integrated risk management in the digital and pandemic era: leveraging on business model canvas framework for an energy services company - Akmal, Mohamad Afiq; Ahmad Dahlan, Abdul Rahman (IIUM, 2022)
Businesses across all sectors are affected by the pandemic and are facing a formidable challenge in terms of digitalisation. The best way to evaluate a company's performance is by having a deep knowledge in their risk management. It is very important that the company have a proper risk management system in place to manage their various risks. This is a requirement for a business company in order to have a proper continuity in operations during this pandemic and digital era. The risk management is a vital part of any company's operations to help them prepare and mitigate against the risks that have been identified. This study aims to explore the various aspects of risk management in Energy Services Company and to discuss the business model using Business Model Canvas [BMC] framework that will enable the company to identify its strategic assets. Thus, building a more effective and relevant Integrated Enterprise Risk Management [IERM] and Risk Management System to ensure business continuity, sustainability, and relevancy.